Analisis Daya Dukung Aksial Dan Penurunan Pondasi Bored Pile Dengan Menggunakan Uji Beban Statik Dan Menggunakan Metode Elemen Hingga Pada Pembangunan Bri-Medan - Mungkur, Bonar Lumsa; Roesyanto, Roesyanto; Harahap, Syiril Erwin; Fischer, Indra Jhon (Syntax Corporation, 2025)
This study analyzes the axial bearing capacity and settlement of a single bored pile foundation with a diameter of 80 cm used in the construction project of the BRI Tower, utilizing static load testing and the Finite Element Method (PLAXIS 3D program). Field data from the Standard Penetration Test (SPT) and cyclic loading test were compared with numerical simulations using the Mohr-Coulomb and Hardening Soil models. The ultimate axial compressive bearing capacity (Qu) of a single bored pile determined analytically using SPT data and the O’Neil and Reese equation is 454.5 tons. The ultimate axial bearing capacity (Qu) of a single bored pile based on loading test data interpreted using the Davisson method is 492.0 tons, the Mazurkiewich method is 464.0 tons, and the Chin method is 416.6 tons. Based on the Finite Element Method (PLAXIS 3D) using the Hardening Soil model, the ultimate axial bearing capacity interpreted using the Davisson method is 497.0 tons, the Mazurkiewich method is 482.0 tons, and the Chin method is 588.2 tons. Meanwhile, the ultimate axial bearing capacity based on the Finite Element Method (PLAXIS 3D) using the Mohr-Coulomb model is 445.0 tons by the Davisson method, 450.0 tons by the Mazurkiewich method, and 714.2 tons by the Chin method. Based on analytical calculations, load tests, and the Finite Element Method, the elastic settlement of a single bored pile was 18.85 mm analytically, 6.13 mm from the loading test, 8.15 mm from the PLAXIS 3D Mohr-Coulomb model, and 6.11 mm from the PLAXIS 3D Hardening Soil model. Overall, the settlements remain within the acceptable tolerance limit (25 mm). Recommendations include the potential for further development of this research by using other analysis software such as MIDAS. Furthermore, future updates to the axial bearing capacity testing standards are suggested, where analysis of foundation bearing capacity may be performed solely using the Finite Element Method (PLAXIS 3D) or other software.